How to think about war : an ancient guide to foreign policy : speeches from the history of the Peloponnesian War - Thucydides (Ancient wisdom for modern readers., 2019)
An accessible modern translation of essential speeches from Thucydides's History that takes readers to the heart of his profound insights on diplomacy, foreign policy, and war.